DESIGN OF TEMPERATURE CONTROL FOR HERBAL DRYER BASED ON PID CONTROLLER BY UTILIZING RENEWABLE ENERGY SOURCES - Heriansyah Heriansyah; Swadexi Istiqphara; Nur Adliani (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2019)
Each type of plant has a different response to light, there are some plants that are very sensitive to direct sunlight and too high temperatures and some that are not. This research will take part in producing automatic medicinal plant drying products using the PID method and with the help of a microcontroller as an input and output processor, which will be used for the herbal medicine industry. The supply of load that will be used in this product comes from a combination of direct sunlight energy and solar panels to produce the right drying method and as needed. When the solar energy received by the dryer is excessive, the microcontroller will order the cooler to work and when the heat received is smaller than what has been set, the microcontroller will order the heater to operate. This product is expected to help the community and herbal medicine businesspeople to produce good quality drugs and can be mass produced. From the results of the research obtained is testing the heating control system, indicating that the control system can control the temperature in order to reach the specified target.